Reinterpreting Narcissism: Sherlock Holmes in Doyle’s “The Final Problem” and BBC’s “The Reichenbach Fall” - Humaira, Dhea; Ashfira, Kartika Dina (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Sherlock Holmes, a famous figure in popular culture, has been continually reinterpreted across different mediums and eras. This study analyzes narcissism in Arthur Conan Doyle’s “The Final Problem” (1893) and its modern adaptation, the BBC series Sherlock, particularly the episode “The Reichenbach Fall” (2012). Using Sigmund Freud’s theory of narcissism, the study examines three core traits of Sherlock’s character: megalomania, lack of empathy, and the need for admiration. Freud’s concepts of primary and secondary narcissism serve as the theoretical framework. The study uses a qualitative approach using an intertextual method to compare the narrative structures, character portrayals, and thematic elements of the two works. The findings reveal that Doyle’s portrayal of Sherlock aligns with Victorian ideals of heroism and intellectual superiority, framing narcissism as a functional trait that aids in his pursuit of justice. In contrast, “The Reichenbach Fall” explores Sherlock’s vulnerabilities, focusing on the emotional consequences of his actions and the collapse of his carefully constructed public image. These differences highlight the evolution of Sherlock’s narcissism from a utilitarian trait in Doyle’s work to a multidimensional characteristic reflecting contemporary anxieties about reputation and identity. The study concludes that the BBC adaptation enriches Doyle’s original portrayal by humanizing Sherlock. This study contributes to both literary and psychoanalytic studies by bridging classic and contemporary perspectives on how narcissism shapes Sherlock Holmes as a literary and cultural icon.